Baking loose powder and preparation method thereof
By combining fillers such as silica treated with hyaluronic acid and emollients, a baked loose powder was prepared, which solved the problem of poor compatibility between existing loose powder and foundation, and improved the skin-friendliness and makeup-holding level.
Patent Information
- Application Number
- CN202411662906.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-25
AI Technical Summary
The compatibility of existing loose powder and foundation is poor, resulting in poor skin-friendly feeling and poor makeup holding.
Fillers such as silica, starch octenyl aluminum succinate, nylon-12 and magnesium stearate treated with hyaluronic acid were prepared by baking and crushing.
It improves the skin-friendliness and makeup-holding degree of loose powder, making it more compatible with the base makeup, making the skin feel more even and easy to apply.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of cosmetics, and in particular to a baked loose powder and a preparation method thereof. Background Art
[0002] Loose powder is a type of facial cosmetics, and its professional name is "setting powder", also known as "honey powder" and "loose white powder". Loose powder does not contain oil and is a powdered product made entirely of powder raw materials. It is mainly applied after foundation emulsion or foundation cream, and is mostly used for post-beauty modification and makeup touch-up to adjust skin tone, prevent greasy skin from being too smooth or too sticky, show a matte but transparent skin color, reduce sweat and sebum, enhance the sustainability of cosmetics, and create a soft, velvety skin feel. Some loose powders also have a certain sunscreen effect, but commonly used loose powders are not compatible with base makeup, which results in poor skin-friendliness and poor makeup durability. Summary of the invention
[0003] In order to improve the skin-friendliness and makeup-lasting effect of loose powder, the present application provides a baked loose powder and a preparation method thereof.
[0004] In the first aspect, the present application provides a baked loose powder, which adopts the following technical solution: A baked loose powder, which is composed of the following components in percentage by weight: 73-92.5% of a filler, 2-6% of a colorant, 1-4% of an emollient A, 0.1-1% of a preservative A, 2-5% of an emollient B, 1-5% of an emulsifier, 1-5% of an emollient C, and 0.1-1% of a preservative B; the filler comprises a mixture of mica, silica treated with hyaluronic acid, corn starch, aluminum starch octenylsuccinate, nylon-12, and magnesium stearate.
[0005] By adopting the above technical scheme, the hyaluronic acid-treated silica in the filler can better fit the skin, starch aluminum octenylsuccinate can reduce greasiness, improve the skin feel of the product, and make it more uniform and easy to apply, nylon-12 can adjust the skin feel, and magnesium stearate has a certain emollient effect. The combination of emollient A, emollient C and preservative B makes the loose powder more compatible with the base makeup, thereby improving the skin-friendliness and makeup durability of the loose powder. In a specific embodiment, the method for preparing the hyaluronic acid-treated silica comprises the following steps: Add isopropanol to triethoxyoctylsilane, stir and mix evenly to obtain a mixed solution A; Add deionized water to the hydrolyzed hyaluronic acid, stir and mix evenly to dissolve the hydrolyzed hyaluronic acid, add mixed solution A while stirring, stir and mix evenly to obtain mixed solution B; Add deionized water to silica, grind, then add lauroyl lysine, continue grinding, then add mixed solution B, continue grinding to obtain a mixture; The mixture is dried and crushed to obtain hyaluronic acid-treated silica.
[0006] By adopting the above technical solution, hyaluronic acid and lauroyl lysine are used to wrap the silica, so that the silica can fit the skin better and improve its skin-friendly performance.
[0007] In a specific embodiment, the colorant includes a mixture of colorant CI 77891, colorant CI 77492, and colorant CI 77499.
[0008] In a specific embodiment, the emollient A includes octyldodecanol stearyloxystearate.
[0009] In a specific embodiment, the preservative A comprises a mixture of phenoxyethanol and caprylyl glycol.
[0010] In a specific embodiment, the emollient B includes a mixture of water, disodium edetate, and glycerin.
[0011] In a specific embodiment, the emulsifier includes polysorbate 80.
[0012] In a specific embodiment, the emollient C includes squalane.
[0013] In a specific embodiment, the preservative B includes phenoxyethanol.
[0014] In the first aspect, the present application provides a method for preparing a baked loose powder, which adopts the following technical solution: A method for preparing roasted loose powder comprises the following steps: Preparation of powder phase A: Stir and mix the filler and the colorant to obtain powder phase A; Preparation of powder phase B: add emollient A and preservative A to powder phase A, stir and mix well to obtain powder phase B; Preparation of emulsion: Heat and stir the emulsifier and emollient C at 60-65°C to obtain an oil phase, heat the emollient B to 80-85°C, then add the oil phase, homogenize, add the preservative B after cooling, stir and mix evenly to obtain an emulsion; Stirring: Add powder phase B into the emulsion and stir it into a fluid state to obtain a material body; Baking: Bake the material at 60-80℃ for 12-16h until the water content of the material is ≤3%; Crushing: Crushing the baked material to obtain roasted loose powder.
[0015] By adopting the above technical scheme, the filler and the colorant are first stirred, and then the emollient A and the preservative A are added and stirred to obtain the powder phase B; the emulsifier and the emollient C are heated and stirred to obtain the oil phase, the emollient B is heated, and then the oil phase is added, homogenized, and the preservative B is added after cooling and stirred to obtain the emulsion; then the powder phase B is added to the emulsion, stirred into a flowing state to obtain the material body, and finally the material body is baked and crushed to obtain the baked loose powder.
[0016] In summary, the present application includes at least one of the following beneficial technical effects: 1. The hyaluronic acid-treated silica in the filler of the present application can better fit the skin, the aluminum starch octenylsuccinate can reduce the greasy feeling, improve the skin feel of the product, make it more uniform and easy to apply, nylon-12 can adjust the skin feel, magnesium stearate has a certain emollient effect, and the combination of emollient A, emollient C and preservative B makes the loose powder more compatible with the base makeup, thereby improving the skin-friendly feeling and makeup lasting degree of the loose powder; 2. In this application, hyaluronic acid and lauroyl lysine are used to encapsulate silica, so that silica can fit the skin better and improve skin-friendly performance; 3. The method of the present application is to first stir the filler and colorant, then add the emollient A and the preservative A, and stir to obtain the powder phase B; heat and stir the emulsifier and the emollient C to obtain the oil phase, heat the emollient B, and then add the oil phase, homogenize, add the preservative B after cooling, and stir to obtain an emulsion; then add the powder phase B to the emulsion, stir into a fluid state, obtain a material body, and finally bake and crush the material body to obtain a baked loose powder. DETAILED DESCRIPTION
[0017] The present application is further described in detail below with reference to the embodiments.
[0018] All raw materials in the examples are commercially available.
[0019] Preparation Example Preparation Example 1 Preparation Example 1 provides a method for preparing hyaluronic acid-treated silica, comprising the following steps: Add isopropanol to triethoxyoctylsilane, stir and mix evenly to obtain a mixed solution A, wherein the weight ratio of triethoxyoctylsilane to isopropanol is 1:2; Deionized water is added to the hydrolyzed hyaluronic acid, and the mixture is stirred and mixed at a speed of 1000 rpm to dissolve the hydrolyzed hyaluronic acid. While stirring, mixed solution A is added, and the mixture is stirred and mixed to obtain mixed solution B; wherein the weight ratio of the hydrolyzed hyaluronic acid to the deionized water is 1:15; the weight ratio of triethoxyoctylsilane to the hydrolyzed hyaluronic acid is 5:2; and the molecular weight of the hydrolyzed hyaluronic acid is less than 400,000 Daltons; Silica is placed in a ball mill, deionized water is added, and the mixture is ground for 1 hour, and then lauroyl lysine is added, and the mixture is ground for 1 hour, and then mixed solution B is added, and the mixture is ground for 2 hours to obtain a mixture; wherein the weight ratio of silica, deionized water, lauroyl lysine, and hydrolyzed hyaluronic acid is 100:300:3:2; The mixture was first dried at 90° C. for 12 h, then dried at 108° C. for 22 h, and then added to a grinder and ground at a rotation speed of 1500 rpm to obtain hyaluronic acid-treated silica. Example
[0020] Example 1 Embodiment 1 provides a method for preparing roasted loose powder, comprising the following steps: Preparation of powder phase A: 92.8 kg of filler and 2 kg of colorant are added to a powder mixing pot, and stirred at a speed of 2500 rpm for 3 minutes to obtain powder phase A; wherein the filler is a mixture of mica, silica treated with hyaluronic acid in Preparation Example 1, corn starch, aluminum starch octenyl succinate, nylon-12, and magnesium stearate, and the weight ratio of mica, silica treated with hyaluronic acid in Preparation Example 1, corn starch, aluminum starch octenyl succinate, nylon-12, and magnesium stearate is 43.7:5:5:25:5:5; the colorant is a mixture of colorant CI 77891, colorant CI 77492, and colorant CI 77499, and the weight ratio of colorant CI 77891, colorant CI 77492, and colorant CI 77499 is 4:0.3:0.3; Preparation of powder phase B: add 1 kg of emollient A and 0.1 kg of preservative A to powder phase A, stir at a speed of 2500 rpm for 3 minutes to obtain powder phase B; wherein the emollient A is octyldodecanol stearyloxystearate; the preservative A is a mixture of phenoxyethanol and caprylyl glycol, and the weight ratio of phenoxyethanol to caprylyl glycol is 13:7; Preparation of emulsion: add 1kg of emulsifier and 1kg of emollient C into an oil pan, heat and stir at 60°C to obtain an oil phase, heat 2kg of emollient B to 80°C in an emulsifier, then slowly add the oil phase into the emulsifier under stirring conditions of 400rpm, homogenize at a speed of 2000rpm for 15min, add 0.1kg of preservative B after cooling, stir at a speed of 2000rpm for 5min to obtain an emulsion; wherein the emulsifier is polysorbate-80; emollient C is squalane; emollient B is a mixture of water, disodium ethylenediaminetetraacetic acid, and glycerin, and the weight ratio of water, disodium ethylenediaminetetraacetic acid, and glycerin is 2:0.5:1; preservative B is phenoxyethanol; Stirring: Add powder phase B into the emulsion and stir for 30 minutes until it becomes a fluid state to obtain a material body; Baking: Bake the material at 60°C for 16 hours until the water content of the material is ≤3%; Crushing: Add the baked material into the powdering pot and crush it at a speed of 2500 rpm for 3 minutes to obtain roasted loose powder.
[0021] Example 2 Embodiment 2 provides a method for preparing roasted loose powder, comprising the following steps: Preparation of powder phase A: add 73 kg of filler and 6 kg of colorant into a powder mixing pot, stir at a speed of 2500 rpm for 3 minutes to obtain powder phase A; wherein the filler is a mixture of mica, silica treated with hyaluronic acid in Preparation Example 1, corn starch, aluminum starch octenyl succinate, nylon-12, and magnesium stearate, and the weight ratio of mica, silica treated with hyaluronic acid in Preparation Example 1, corn starch, aluminum starch octenyl succinate, nylon-12, and magnesium stearate is 43.7:5:5:25:5:5; the colorant is a mixture of colorant CI 77891, colorant CI 77492, and colorant CI 77499, and the weight ratio of colorant CI 77891, colorant CI 77492, and colorant CI 77499 is 4:0.3:0.3; Preparation of powder phase B: add 4 kg of emollient A and 1 kg of preservative A to powder phase A, stir at a speed of 2500 rpm for 3 minutes to obtain powder phase B; wherein the emollient A is octyldodecanol stearyloxystearate; the preservative A is a mixture of phenoxyethanol and caprylyl glycol, and the weight ratio of phenoxyethanol to caprylyl glycol is 13:7; Preparation of emulsion: add 5kg of emulsifier and 5kg of emollient C into an oil pan, heat and stir at 60°C to obtain an oil phase, heat 5kg of emollient B to 80°C in an emulsifier, then slowly add the oil phase into the emulsifier under stirring at 400rpm, homogenize at 2000rpm for 15min, add 1kg of preservative B after cooling, stir at 2000rpm for 5min to obtain an emulsion; wherein the emulsifier is polysorbate 80; emollient C is squalane; emollient B is a mixture of water, disodium ethylenediaminetetraacetic acid and glycerin, and the weight ratio of water, disodium ethylenediaminetetraacetic acid and glycerin is 2:0.5:1; preservative B is phenoxyethanol; Stirring: Add powder phase B into the emulsion and stir for 30 minutes until it becomes a fluid state to obtain a material body; Baking: Bake the material at 60°C for 16 hours until the water content of the material is ≤3%; Crushing: Add the baked material into the powdering pot and crush it at a speed of 2500 rpm for 3 minutes to obtain roasted loose powder.
[0022] Example 3 Embodiment 3 provides a method for preparing roasted loose powder, comprising the following steps: Preparation of powder phase A: 83 kg of filler and 4 kg of colorant are added to a powder mixing pot, and stirred at a speed of 2500 rpm for 3 minutes to obtain powder phase A; wherein the filler is a mixture of mica, silica treated with hyaluronic acid in Preparation Example 1, corn starch, aluminum starch octenyl succinate, nylon-12, and magnesium stearate, and the weight ratio of mica, silica treated with hyaluronic acid in Preparation Example 1, corn starch, aluminum starch octenyl succinate, nylon-12, and magnesium stearate is 43.7:5:5:25:5:5; the colorant is a mixture of colorant CI 77891, colorant CI 77492, and colorant CI 77499, and the weight ratio of colorant CI 77891, colorant CI 77492, and colorant CI 77499 is 4:0.3:0.3; Preparation of powder phase B: add 2.5 kg of emollient A and 0.5 kg of preservative A to powder phase A, stir at a speed of 2500 rpm for 3 minutes to obtain powder phase B; wherein the emollient A is octyldodecanol stearyloxystearate; the preservative A is a mixture of phenoxyethanol and caprylyl glycol, and the weight ratio of phenoxyethanol to caprylyl glycol is 13:7; Preparation of emulsion: add 3kg of emulsifier and 3kg of emollient C into an oil pan, heat and stir at 60°C to obtain an oil phase, heat 3.5kg of emollient B to 80°C in an emulsifier, then slowly add the oil phase into the emulsifier under stirring conditions of 400rpm, homogenize at a speed of 2000rpm for 15min, add 0.5kg of preservative B after cooling, stir at a speed of 2000rpm for 5min to obtain an emulsion; wherein the emulsifier is polysorbate-80; emollient C is squalane; emollient B is a mixture of water, disodium ethylenediaminetetraacetic acid, and glycerin, and the weight ratio of water, disodium ethylenediaminetetraacetic acid, and glycerin is 2:0.5:1; preservative B is phenoxyethanol; Stirring: Add powder phase B into the emulsion and stir for 30 minutes until it becomes a fluid state to obtain a material body; Baking: Bake the material at 60°C for 16 hours until the water content of the material is ≤3%; Crushing: Add the baked material into the powdering pot and crush it at a speed of 2500 rpm for 3 minutes to obtain roasted loose powder.
[0023] Example 4 The difference between Example 4 and Example 2 is that, in the preparation of the emulsion, 3 kg of emulsifier and 3 kg of emollient C are added to an oil pan, heated and stirred at 62.5°C to obtain an oil phase, 3.5 kg of emollient B is heated to 82.5°C in an emulsifying pan, and then the oil phase is slowly added to the emulsifying pan under stirring conditions of 400 rpm, homogenized at a speed of 2000 rpm for 15 minutes, and after cooling, 0.5 kg of preservative B is added, and stirred at a speed of 2000 rpm for 5 minutes to obtain an emulsion; wherein the emulsifier is polysorbate 80; the emollient C is squalane; the emollient B is a mixture of water, disodium ethylenediaminetetraacetic acid, and glycerin, and the weight ratio of water, disodium ethylenediaminetetraacetic acid, and glycerin is 2:0.5:1; the preservative B is phenoxyethanol; Stirring: Add powder phase B into the emulsion and stir for 30 minutes until it becomes a fluid state to obtain a material body; Baking: Bake the material at 70°C for 14 hours until the water content of the material is ≤3%; Crushing: Add the baked material into a powder-beating pot and crush it at a rotation speed of 2500 rpm for 3 minutes to obtain roasted loose powder; the remaining steps are consistent with Example 2.
[0024] Example 5 The difference between Example 5 and Example 2 is that, in the preparation of the emulsion, 3 kg of emulsifier and 3 kg of emollient C are added to an oil pan, heated and stirred at 65° C. to obtain an oil phase, 3.5 kg of emollient B is heated to 85° C. in an emulsifying pan, and then the oil phase is slowly added to the emulsifying pan under stirring conditions of 400 rpm, homogenized at a speed of 2000 rpm for 15 min, and after cooling, 0.5 kg of preservative B is added, and stirred at a speed of 2000 rpm for 5 min to obtain an emulsion; wherein the emulsifier is polysorbate 80; the emollient C is squalane; the emollient B is a mixture of water, disodium ethylenediaminetetraacetic acid, and glycerin, and the weight ratio of water, disodium ethylenediaminetetraacetic acid, and glycerin is 2:0.5:1; the preservative B is phenoxyethanol; Stirring: Add powder phase B into the emulsion and stir for 30 minutes until it becomes a fluid state to obtain a material body; Baking: Bake the material at 80°C for 12 hours until the water content of the material is ≤3%; Crushing: Add the baked material into a powder-beating pot and crush it at a rotation speed of 2500 rpm for 3 minutes to obtain roasted loose powder; the remaining steps are consistent with Example 2.
[0025] Example 6 The difference between Example 6 and Example 4 is that the emollient B is a mixture of water and disodium edetate, and the weight ratio of water to disodium edetate is 2:0.5; the remaining steps are consistent with Example 4.
[0026] Example 7 The difference between Example 7 and Example 4 is that the emollient B is a mixture of water and glycerin, and the weight ratio of water to glycerin is 2:1; the remaining steps are consistent with Example 4.
[0027] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the filler is a mixture of mica, corn starch and magnesium stearate, and the weight ratio of mica, corn starch and magnesium stearate is 43.7:5:5; the remaining steps are consistent with Example 1.
[0028] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the filler is a mixture of mica, starch octenyl succinate aluminum, and nylon-12, and the weight ratio of mica, starch octenyl succinate aluminum, and nylon-12 is 43.7:25:5; the remaining steps are consistent with Example 1.
[0029] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the filler is a mixture of mica, corn starch, aluminum starch octenylsuccinate, nylon-12, and magnesium stearate, and the weight ratio of mica, corn starch, aluminum starch octenylsuccinate, nylon-12, and magnesium stearate is 43.7:5:25:5:5; the remaining steps are consistent with Example 1.
[0030] Performance testing Skin feel test: 100 healthy Chinese women aged 25-45 years old with no obvious facial trauma and disease and dry cheekbones from the same region were recruited and divided into 10 experimental groups, corresponding to Examples 1-7 and Comparative Examples 1-3, respectively; cleansed their faces at 8 a.m., then applied 0.2 g of the baked loose powder in the examples or comparative examples on the cheekbones of the right cheek, and then scored, with a scoring standard of 1-10 points, the higher the score for better skin feel, the lower the score for poor skin feel, and the average value of each group was taken.
[0031] Makeup lasting degree test: 100 healthy Chinese women aged 25-45 years old with no obvious facial trauma and disease and dry cheekbones from the same region were recruited and divided into 10 experimental groups, corresponding to Examples 1-7 and Comparative Examples 1-3 respectively; cleansed the face at 8 o'clock in the morning, then applied 0.2g of the baked loose powder in the embodiment or comparative example on the cheekbones of the right cheek, then ran on a treadmill at 35°C at a speed of 10km / h. After running for 10 minutes, the experimental subjects all sweated; rested for 10 minutes after every 20 minutes of running; after 3 hours, stopped exercising, observed the makeup removal, and scored. The scoring standard was 1-10 points. The smaller the makeup removal, the higher the score, and if the makeup removal was higher, the lower the score. The average value was taken for each group.
[0032] Table 1 Performance test results of baked loose powder sample Skin-friendly score Makeup lastingness score Example 1 8.5 8.8 Example 2 8.6 8.9 Example 3 8.9 9.1 Example 4 9.2 9.4 Example 5 9.0 9.2 Example 6 8.8 9.3 Example 7 8.9 9.4 Comparative Example 1 7.7 8.5 Comparative Example 2 8.0 8.3 Comparative Example 3 7.9 8.3 In combination with Example 1 and Comparative Examples 1-3, the baked loose powder in Example 1 has the best skin-friendliness and makeup-lasting effect. It can be seen that when preparing powder phase A, the filler is preferably a mixture of mica, hyaluronic acid-treated silica, corn starch, starch octenyl succinate aluminum, nylon-12, and magnesium stearate. The silica treated with hyaluronic acid can better fit the skin, starch octenyl succinate aluminum can reduce greasiness and improve the skin feel of the product, nylon-12 can adjust the skin feel, and magnesium stearate has a certain emollient effect. The combination of emollient A, emollient C and preservative B makes the loose powder more compatible with the base makeup, thereby improving the skin-friendliness and makeup-lasting effect of the baked loose powder.
[0033] In combination with Examples 1-3, the baked loose powder in Example 3 has the best skin-friendly feel and makeup-lasting degree, which shows that when preparing the baked loose powder, the raw material ratio in Example 3 is the best.
[0034] In combination with Examples 3-5, the baked loose powder in Example 4 has the best skin-friendly feel and makeup-lasting degree, which shows that when preparing the baked loose powder, the preparation conditions in Example 4 are the best.
[0035] Combining Example 4, Example 6 and Example 7, the baked loose powder in Example 4 has the best skin-friendly feel. It can be seen that when preparing the emulsion, the emollient B is preferably a mixture of water, disodium ethylenediaminetetraacetic acid, and glycerin, and the skin-friendly effect of the baked loose powder is better.
[0036] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A baked loose powder, characterized in that: The baked loose powder is composed of the following components in percentage by weight: filler 73-92.5%, colorant 2-6%, emollient A 1-4%, preservative A 0.1-1%, emollient B 2-5%, emulsifier 1-5%, emollient C 1-5%, preservative B 0.1-1%; the filler includes a mixture of mica, hyaluronic acid-treated silica, corn starch, aluminum starch octenylsuccinate, nylon-12, and magnesium stearate.
2. The baked loose powder according to claim 1, characterized in that: The preparation method of the hyaluronic acid-treated silica comprises the following steps: Add isopropanol to triethoxyoctylsilane, stir and mix evenly to obtain a mixed solution A; Add deionized water to the hydrolyzed hyaluronic acid, stir and mix evenly to dissolve the hydrolyzed hyaluronic acid, add mixed solution A while stirring, stir and mix evenly to obtain mixed solution B; Add deionized water to silica, grind, then add lauroyl lysine, continue grinding, then add mixed solution B, continue grinding to obtain a mixture; The mixture is dried and crushed to obtain hyaluronic acid-treated silica.
3. The baked loose powder according to claim 1, characterized in that: The colorant includes a mixture of colorant CI 77891, colorant CI 77492, and colorant CI 77499.
4. The baked loose powder according to claim 1, characterized in that: The emollient A includes octyldodecanol stearyloxystearate.
5. The baked loose powder according to claim 1, characterized in that: The preservative A comprises a mixture of phenoxyethanol and caprylyl glycol.
6. The baked loose powder according to claim 1, characterized in that: The emollient B comprises a mixture of water, disodium edetate and glycerin.
7. The baked loose powder according to claim 1, characterized in that: The emulsifier includes polysorbate-80.
8. The baked loose powder according to claim 1, characterized in that: The emollient C includes squalane.
9. The baked loose powder according to claim 1, characterized in that: The preservative B includes phenoxyethanol.
10. A method for preparing the roasted loose powder according to any one of claims 1 to 9, characterized in that: The following steps are involved: Preparation of powder phase A: Stir and mix the filler and the colorant to obtain powder phase A; Preparation of powder phase B: add emollient A and preservative A to powder phase A, stir and mix well to obtain powder phase B; Preparation of emulsion: Heat and stir the emulsifier and emollient C at 60-65°C to obtain an oil phase, heat the emollient B to 80-85°C, then add the oil phase, homogenize, add the preservative B after cooling, stir and mix evenly to obtain an emulsion; Stirring: Add powder phase B into the emulsion and stir it into a fluid state to obtain a material body; Baking: Bake the material at 60-80℃ for 12-16h until the water content of the material is ≤3%; Crushing: Crushing the baked material to obtain roasted loose powder.